PENGARUH KUALITAS PRODUK DAN DAYA TARIK IKLAN TERHADAP KEPUTUSAN PEMBELIAN DAN MINAT BELI ULANG PRODUK EYELINER MEREK MAYBELLINE DI KOTA PEKANBARU - Rana, Koswita; Sri, Restuti; Marhadi, Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the effect of product quality and advertisingattractiveness on repurchasing interest through purchasing decisions as anintervening variable in Maybeline brand Eyeliner products in Pekanbaru City Thepopulation in this study were all customers of the Maybelline brand Eyelinerproducts in Pekanbaru and unknown in number. The sample selection usesaccidental sampling. The sample used in this study amounted to 120. The types ofdata used were primary and secondary data, while the data collection techniquesused questionnaires and library studies. Data analysis using path analysis. Theresults showed that the quality of products and the attractiveness of advertisingpartially had a significant effect on purchasing decisions, the decision had asignificant effect on repurchase interest. Product quality and ad attractivenesshave a significant effect on repurchasing interest through purchasing decisions.Keywords : product quality, ad appeal, purchasing decision, repurchase interest